Studying Replacement of Medical Equipment in the Radiology Department in a Local Hospital by Using Artificial Intelligence Algorithms - حلوم ميس (Latakia University Journal -Engineering Sciences Series, 2025)
The management of medical equipment is considered an important part in hospitals management, where good management of medical equipment leads to safe and effective use through medical equipment life cycle. In this research, an expert system was built for managing medical equipment and its replacement. This system takes into consideration numbers of parameters that effect replacement decision, where Inference engine deals with input parameters according to the two types: Fuzzy Logic and Decision Tree. We applied our expert system on some medical equipment in the radiology department in Tishreen University Hospital in Lattakia, and the results in the output showed the efficiency of our system for determining the medical equipment replacement.